CITRA DESTINASI DAN PRODUK WISATA BERPENGARUH TERHADAP KEPUASAN DAN LOYALITAS PENGUNJUNG PANTAI SLOPENG DI KABUPATEN SUMENEP - Humairoh, Tuffahul; Andriani, Nurita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Slopeng Beach is an ideal place to unwind and enjoy the view. On the other hand, Slopeng Beach has received a lot of bad feedback from visitors. This study aims to analyse the relationship effects of destination image, tourism products, visitor satisfaction and destination loyalty of Slopeng Beach in Sumenep District. A quantitative strategy was used in the study, which involved the use of a survey instrument called a questionnaire. Using the SmartPLS (partial least squares) approach, regression analysis and Structura lEquation Model (SEM) were used for analysis. The results of this study reveal that destination image has a positive effect on visitor satisfaction, tourism products show a positive effect on satisfaction, visitor satisfaction variables have a positive effect on loyalty, Destination Image has a positive effect on Loyalty, and Tourism Products have an insignificant negative effect on Loyalty. In addition, destination image and tourism products have an influence on loyalty through visitor satisfaction.